Exploring photosynthetic biodiversity of the Ross Sea (Antarctica): how environmental changes affect it? - TRENTIN, RICCARDO (Università degli studi di Padova, 2024)
Antarctic algae are important primary producers with a key role in ecosystems functioning of the Southern Ocean. A comprehensive study of algal diversity, from genes to ecology, is crucial to shed light on their complex evolutionary history and in understanding the impact of human activities to Antarctic life. The present thesis explored algal diversity of Terra Nova Bay (Ross Sea, Antarctica) and its response to anthropogenic environmental changes. An integrative approach was carried out to assess the systematic position of microalgae, isolated from seawater, sea–ice and filters of the desalination plant from Mario Zucchelli research station, and seaweeds, collected during several Italian Antarctic Expeditions. The use of integrative taxonomy was pivotal in providing new insights into morphological, molecular, ecological and chemical diversity of Antarctic algae and led to the description of a new genus and a new species of Antarctic non–geniculate coralline alga, Thalassolithon adeliense, a new species of unicellular green algae, Microglena antarctica, and three new species of diatoms, namely Craspedostauros ineffabilis, Craspedostauros zucchellii and Gedaniella antarctica. Despite being small additions to our knowledge of algae from Terra Nova Bay, these taxa could be used as references for future studies on local diversity in relation to ongoing environmental changes. In fact, polar regions are considered particularly sensitive to anthropic activities which might severely impact local biota. Moreover, this work evaluated the effects of two stressors, temperature and lead (Pb), on Microglena antarctica and Iridaea cordata, important species in sea–ice and benthic communities, respectively. In doing this, well–known end points used in the evaluation of stress responses and emerging tools in the study of metabolic responses of algae (untargeted metabolomics approach) were employed. These tests highlighted species– and stress– specific responses and suggested that a pool of data resulting from physiological, ...